2021
DOI: 10.3389/fnbeh.2021.655449
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Working Memory Performance in the APPswe/PSEN1dE9 Mouse Model of Alzheimer’s Disease Using an Automated Figure-8-Maze

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, with a long preclinical and prodromal phase. To enable the study of disease mechanisms, AD has been modeled in many transgenic animal lines and cognitive functioning has been tested using several widely used behavioral tasks. These tasks, however, are not always suited for repeated longitudinal testing and are often associated with acute stress such as animal transfer, handling, novelty, or stress related to the task itself. This makes it ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“… 19 In addition, repeat testing of the same animal can impact behavioural tasks, as animals will habituate and learn tasks over time, which may affect their behaviour. 53 Indeed, we have previously shown that a mouse model of anxiety has different whisker movements to control mice 24 ; therefore, an altered sensitivity to stress is likely to affect our results. The lack of automation of our set‐up may also confound testing over different ages, while here we made sure that all data was collected over a period of just a few days, with all the equipment kept the same throughout.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“… 19 In addition, repeat testing of the same animal can impact behavioural tasks, as animals will habituate and learn tasks over time, which may affect their behaviour. 53 Indeed, we have previously shown that a mouse model of anxiety has different whisker movements to control mice 24 ; therefore, an altered sensitivity to stress is likely to affect our results. The lack of automation of our set‐up may also confound testing over different ages, while here we made sure that all data was collected over a period of just a few days, with all the equipment kept the same throughout.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, it is rather difficult to conduct such a study, especially to 17 months, due to the increased mortality rates in older 3xTg‐AD mice 19 . In addition, repeat testing of the same animal can impact behavioural tasks, as animals will habituate and learn tasks over time, which may affect their behaviour 53 . Indeed, we have previously shown that a mouse model of anxiety has different whisker movements to control mice 24 ; therefore, an altered sensitivity to stress is likely to affect our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we successfully implemented a novel behavioral task that tests the ability of mice to follow the correct path and to retrieve a reward, based solely on the spatial context presented. Although similar automated maze devices were constructed previously [11,12,[15][16][17][18], and the T-Maze protocol has been tested in a plethora of previous studies [10,[19][20][21][22][23], it was always used in the win-shift arrangement, where spatial information merely supported the rule learning. The animals had to remember the given spatial orientation and utilize it to choose the opposite arm during the choice phase.…”
Section: Discussionmentioning
confidence: 99%
“…We designed and implemented an automated, semi-autonomous system for spatial memory tests. It is based on the T-Maze paradigm [9][10][11][12], with modifications allowing for reliable dependence on visual cues. It allows for a relatively high throughput with minimum human intervention.…”
Section: Introductionmentioning
confidence: 99%